Possible Rates of Detection of Neonatal Sepsis Pathogens in the Context of Microbiological Diagnostics in Mothers – Real World Data - Kuld, Raffael; Krauth, Alexander; Kühr, Joachim; Krämer, Janine; Dittrich, Ralf; Häberle, Lothar; Müller, Andreas (Geburtshilfe und Frauenheilkunde, 2023)
Objective The aim of this study was to identify the rate of detection of neonatal sepsis pathogens in maternal microbiological smears. Study Design This is a retrospective study conducted at a Level 1 perinatal center in the context of routine care from 2014 to 2019. For all premature infants and neonates with neonatal sepsis, the neonatal and maternal microbiological findings were examined to see if there was a match. Results During the study period, a total of 948 premature or newborn infants were identified as having a neonatal infection. Among all of the premature or newborn infants, 209 (22%) met the diagnostic criteria for neonatal sepsis; of these, 157 were premature births and 52 were full-term births. We evaluated the microbiological findings for these 209 mother and child pairs. No pathogens were detected in 27 out of 157 mothers of premature infants (17.1%) and in 31 out of 52 mothers of full-term infants (59.6%). In the premature infant group there were pairs with matching pathogens in 30 out of 130 cases (23.1%, 95% CI: 16.1-31.3), and in the full-term infant group there was a match in 4 out of 21 cases (19%, 95% CI: 5.4-41.9). The number needed to test to have a 90% probability of success for pathogen detection varies between 9 and 11 in the most favorable case and 26 and 32 in the least favorable case, depending on the evaluation method. Conclusion In cases of neonatal sepsis, the sepsis-causing pathogen was successfully detected through prior analysis of a maternal smear in 7% of full-term infants and in 19% of premature infants. The number needed to test was relatively high in all groups. The value of maternal smears for identifying neonatal sepsis-causing pathogens needs to be critically questioned.
CRIS-Team Scopus Importer:2023-12-08
Keywords: bacterial infection; infections; normal birth; pregnancy; premature birth